Pengaruh Kualitas Pelayanan Dan Kepuasan Pasien Terhadap Loyalitas Pasien Rawat Jalan Pada Industri Jasa Rumah Sakit (Journal of Hospital Management, 2020)
This study aims to analyze the influence of service quality and patient satisfaction on the trust and loyalty of patients in health care industri. The research period is during August 2018-January 2019. The design of this study is explanatory causality (Explanatory Research). Categorized into one shot case study. The sample in this study were 100 outpatients who had visited at least 2 visits with a minimum age of 20 years. The research instrument used a questionnaire using the Likert scale 1-4. This study uses PLS SEM analysis. The results showed that one of the factors that led to high patient loyalty was service quality such as tangibles, reliability and empathy. Therefore, it is important for the management to improve the quality of the service so that it becomes even better. Perception about the quality of good service will result in the emergence of satisfaction, trust and even loyalty, thus will support the implementation of the hospital strategy and the achievement of hospital goals.Keyword: Patient loyalty, patient trust, service quality and patient satisfaction